Évaluation de la marchabilité de trois environnements urbains de la région métropolitaine montréalaise à partir de l’outil MAPPA - François Raulin; Sébastien Lord; Paula Negron-Poblete (VertigO)
The walk became a public health priority in urban planning. In addition, walking need to be included in combination with almost all types of transport. However, walking is not always possible or enjoyable or even feasible within different urban environments. Some areas can be described as not “walkable” like the suburbs, while others correspond to the assumption that the central neighbourhoods are more favourable to pedestrians. By exploring the concept of walkability and using the MAPPA tool, we evaluate in the study three residential neighbourhoods in the greater Montréal. To compare neighbourhoods, we constructed a typology that classifies street segments from their low to more walkability potential. These three urban areas were chosen in terms of various economic phases that succeeded historically in the province of Québec: 1) Old Rosemont - former working class neighbourhood; 2) Duvernay - Laval - postwar suburbs; 3) Bois-Franc - Saint-Laurent District - new urbanism. In a working class neighbourhood built before automobile standards, walkability is high and there are many proximity destinations. In the suburbs, walkability is not as low as what we assumed. Urban form developed around the car offers good walkability, which is essentially local and leisure related. In the New Urbanism neighbourhood, the vast majority of streets offer excellent walkability. The least favourable street segments are those leading to amenities. Although, a good walkability planned on paper is not enough without the planning of mixed and functional diversity.